Photoelectron circular dichroism in different ionization regimes - Matthias Wollenhaupt (New Journal of Physics, 2016)
Photoelectron circular dichroism (PECD) describes an asymmetry in the photoelectron angular distribution (PAD) from photoionization of randomly oriented enantiomers with circularly polarized light. Beaulieu et al present a comprehensive set of measured PADs from multiphoton ionization of limonene and fenchone in different ionization regimes (multiphoton and tunneling) and analyze the resulting PECD (Beaulieu et al 2016 New J. Phys. http://dx.doi.org/10.1088/1367-2630/18/10/102002 18 http://dx.doi.org/10.1088/1367-2630/18/10/102002 ). From their observations the authors conclude that the PECD is universal in the sense that the molecular chirality is encoded in the PAD independent of the ionization regime. The analysis is supplemented by a classical model based on electron scattering in a chiral potential. The paper presents beautiful data and is an important step towards a more complete physical picture of PECD. The results and their interpretation stimulate the ongoing vivid debate on the role of resonances in multiphoton PECD.